Dynamic distress calls: volatile info chemicals induce and regulate defense responses during herbivory - Kutty, Nithya N.; Mishra, Manasi (Frontiers in Plant Science, 2023)
Plants are continuously threatened by a plethora of biotic stresses caused by microbes, pathogens, and pests which often act as the major constraint in crop productivity. To overcome such attacks, plants have evolved with an array of constitutive and induced defense mechanisms – morphological, biochemical, and molecular. Volatile organic compounds (VOCs) are a class of specialized metabolites which are naturally emitted by plants and play an important role in plant communication and signaling. During herbivory and mechanical damage, plants also emit an exclusive blend of volatiles often referred to as herbivore-induced plant volatiles (HIPVs). The composition of this unique aroma bouquet is dependent upon the plant species, developmental stage, environment, and herbivore species. HIPVs emitted from infested and non-infested plant parts can prime plant defense responses by various mechanisms such as redox, systemic and jasmonate signaling, activation of mitogen-activated protein (MAP) kinases, transcription factors, mediate histone modifications and can also modulate the interactions with natural enemies via direct and indirect mechanisms. These specific volatile cues mediate allelopathic interactions leading to altered transcription of defense-related genes viz. proteinase inhibitors, amylase inhibitors in neighboring plants, and enhanced levels of defense-related secondary metabolites like terpenoids and phenolic compounds. These factors act as deterrents to feeding insects, attract parasitoids and provoke behavioral changes in plants and their neighboring species. This review presents an overview of the plasticity identified in HIPVs and their role as regulators of plant defense in Solanaceous plants. The selective emission of green leaf volatiles (GLVs) including hexanal and its derivatives, terpenes, methyl salicylate, and methyl jasmonate (MeJa) inducing direct and indirect defense responses during an attack from phloem-sucking and leaf-chewing pests is discussed. Further, we also focus on the recent developments in the field of metabolic engineering focused on modulation of the volatile bouquet to improve plant defenses.